(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
This chapter presents a physical description, details of location, extent of erosion, method of access to the stack and an account of previous work. A linear and large drystone rectangular wall or blockhouse enclosed at least six structures on top of the stack. These structures consisted of curving lines of turf-covered wall footings, supported by revetment walls at the cliff edge. There are no exposed and eroding soil layers as the plateau of the stack is above the reach of most wave action. The deterioration is caused by the undermining of structural remains which collapse as the underlying rock gives way.